Sonic branding: a narrative review at the intersection of art and science - Spence, C; Keller, S (Wiley, 2024)
The field of sonic branding/marketing has grown rapidly in recent years, as has commercial interest in more science-based approaches to the practice, particularly as more brands and agencies look for qualitative and quantitative evidence to support the efficacy of sonic branding. In this research note, we explore the ways in which the design and execution (i.e., the “art”) of sonic branding initiatives can be informed by overlapping approaches and techniques drawn from the sciences, namely psychoacoustics, semiotics, music/auditory cognition, and crossmodal research. We explore whether the rapid growth of generative AI may represent the next major evolution in the design, creation, and assessment of sonic assets, where science and art are used to train AI tools that could one day augment (and potentially disrupt) the work of human sound designers and composers. These developments notwithstanding, it is argued that sonic branding will likely remain as much an art as a science, though basing one's approach on the emerging scientific literature ought to at least tilt the odds of success in the creative's favor.